RETRACTED: SHCBP1 Promotes Papillary Thyroid Carcinoma Carcinogenesis and Progression Through Promoting Formation of Integrin and Collagen and Maintaining Cell Stemness - Geng, Houfa; Guo, Mengzhe; Xu, Wei; Zang, Xiu; Wu, Tingting; Teng, Fei; Wang, Yu; Liu, Xuekui; Wang, Xiuli; Sun, Qiang; Liang, Jun (Frontiers in Endocrinology, 2021)
Papillary thyroid carcinoma (PTC) is the most common thyroid cancer with a rapidly increasing incidence globally. Bioinformatics analyses suggested that SHCBP1 (SHC SH2 Domain-Binding Protein 1) was significantly up-regulated in PTC tumor tissues, which was further confirmed by immunohistochemical staining and qPCR analyses in Xuzhou cohort. Moreover, the results indicated that the mRNA level of SHCBP1 was negatively associated with patients’ disease-free survival rate, and further analysis reveals that patients with high SHCBP1 expression tend to have more lymph node metastasis. Afterward, MTT, colony formation, cell-cycle assay, FACS apoptosis assay, invasion, migration, as well as scratch assay were performed to study the phenotypes change of PTC cells after knocking down SHCBP1. The in vivo subcutaneous tumor model was developed to study the proliferation ability of PTC cells after SHCBP1 knockdown. We show that knock down of SHCBP1 significantly inhibits PTC cell proliferation, cell cycle, invasion and migration in vivo and in vitro. Western blot and qRT-PCR showed that knockdown of SHCBP1 could significantly reduce MYC, KLF4, CD44, ITGA6, ITGB1, ITGB5, and COL4A2 expression at both RNA and protein levels, which indicated that SHCBP1 might be involved in PTC carcinogenesis and progression through targeting formation of integrin and collagen and cell stemness pathways, and can be a potential diagnosis biomarker and therapeutic target for PTC.